Answer:
i think ur question is wrong
Answer:
It is not equivalent.
Step-by-step explanation:
You have to expand the brackets :
(x-4)(x+3)
= x(x) + x(3) - 4(x) - 4(3)
= x² + 3x - 4x - 12
= x² - x - 12
Therefore, x² - x - 12 / (x-4)(x+3) is not equivalent to x² - 4x - 12.
Answer:
60 percent i hope this helped.
Step-by-step explanation:
each have a a possibility of 10 and there's 6 of of 10 compared to 3 out of 10.
Answer:
Final answer is ![x-6y=23](https://tex.z-dn.net/?f=x-6y%3D23)
Step-by-step explanation:
We need to find the equation of the line that is parallel to x=6y-5 and that passes through (5,-3).
So first we need to find the slope of given line.
rewirite x=6y-5 in y=mx+b form
x+5=6y
![\frac{1}{6}x+\frac{5}{6}=y](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7Dx%2B%5Cfrac%7B5%7D%7B6%7D%3Dy)
Compare given equation with y=mx+b
we get: m=1/6
We know that parallel equations has equal slope.
Then slope of required line m=1/6
Now plug the given point (5,-3) and slope m=1/6 into point slope formula:
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y-(-3)=\frac{1}{6}\left(x-5\right)](https://tex.z-dn.net/?f=y-%28-3%29%3D%5Cfrac%7B1%7D%7B6%7D%5Cleft%28x-5%5Cright%29)
![y+3=\frac{1}{6}x-\frac{5}{6}](https://tex.z-dn.net/?f=y%2B3%3D%5Cfrac%7B1%7D%7B6%7Dx-%5Cfrac%7B5%7D%7B6%7D)
![y=\frac{1}{6}x-\frac{5}{6}-3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B6%7Dx-%5Cfrac%7B5%7D%7B6%7D-3)
![y=\frac{1}{6}x-\frac{23}{6}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B6%7Dx-%5Cfrac%7B23%7D%7B6%7D)
Now we need to rewrite that equation in standard form. Ax+By=C.
6y=x-23
x-23=6y
x-6y=23
Hence final answer is ![x-6y=23](https://tex.z-dn.net/?f=x-6y%3D23)